Soil properties and sediment accretion modulate methane fluxes from restored wetlands. (10th April 2018) - Chamberlain, Samuel D.; Anthony, Tyler L.; Silver, Whendee L.; Eichelmann, Elke; Hemes, Kyle S.; Oikawa, Patricia Y.; Sturtevant, Cove; Szutu, Daphne J.; Verfaillie, Joseph G.; Baldocchi, Dennis D.
Abstract: Wetlands are the largest source of methane (CH4 ) globally, yet our understanding of how process‐level controls scale to ecosystem fluxes remains limited. It is particularly uncertain how variable soil properties influence ecosystem CH4 emissions on annual time scales. We measured ecosystem carbon dioxide (CO2 ) and CH4 fluxes by eddy covariance from two wetlands recently restored on peat and alluvium soils within the Sacramento–San Joaquin Delta of California. Annual CH4 fluxes from the alluvium wetland were significantly lower than the peat site for multiple years following restoration, but these differences were not explained by variation in dominant climate drivers or productivity across wetlands. Soil iron (Fe) concentrations were significantly higher in alluvium soils, and alluvium CH4 fluxes were decoupled from plant processes compared with the peat site, as expected when Fe reduction inhibits CH4 production in the rhizosphere. Soil carbon content and CO2 uptake rates did not vary across wetlands and, thus, could also be ruled out as drivers of initial CH4 flux differences. Differences in wetland CH4 fluxes across soil types were transient; alluvium wetland fluxes were similar to peat wetland fluxes 3 years after restoration. Changing alluvium CH4 emissions with time could not be explained by an empirical model based on dominant CH4 flux biophysical drivers, suggesting that other factors, not measured by our eddy covariance towers, were responsible for these changes. Recently accreted alluvium soils were less acidic and contained more reduced Fe compared with the pre‐restoration parent soils, suggesting that CH4 emissions increased as conditions became more favorable to methanogenesis within wetland sediments. This study suggests that alluvium soil properties, likely Fe content, are capable of inhibiting ecosystem‐scale wetland CH4 flux, but these effects appear to be transient without continued input of alluvium to wetland sediments. Abstract : Legacy soil properties may influence current greenhouse gas fluxes from restored wetlands, but soil interactions with ecosystem‐scale methane emissions are often uncertain. Using an eddy covariance tower network, we observed substantially reduced methane emissions from wetlands restored on high iron, alluvium soils compared with nearby sites restored on peat soils; however, these differences disappeared multiple years postrestoration as new wetland soils were accreted. Our results demonstrate how soil properties can regulate methane fluxes from restored wetlands, though these effects are short in duration compared with the lifetime of wetland restoration projects.